2021
DOI: 10.33393/grhta.2021.2191
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of caplacizumab in the new standard of care for immune Thrombotic Thrombocytopenic Purpura in Italy

Abstract: Objectives: To evaluate the cost-effectiveness analysis (CEA) of caplacizumab in combination with plasmapheresis (PEX) and immunosuppression compared to PEX and immunosuppression in the treatment of acute episodes of iTTP. Methods: A Markov model was used to conduct the CEA from the perspective of the hospital, over a lifetime horizon. Clinical data derived from HERCULES trial and a systematic literature review. Economic input included direct costs only. Utility and disutility values were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Most recent studies have demonstrated that adding caplacizumab to TPE and immunosuppressives is cost-effective. 69,80 It allows the hospital to achieve a greater efficiency in managing a life-threatening disease like iTTP.…”
Section: Ther Apeuti C S Tr Ategy For Acute It Tpmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent studies have demonstrated that adding caplacizumab to TPE and immunosuppressives is cost-effective. 69,80 It allows the hospital to achieve a greater efficiency in managing a life-threatening disease like iTTP.…”
Section: Ther Apeuti C S Tr Ategy For Acute It Tpmentioning
confidence: 99%
“…Thus, it is important to stop microvascular thrombosis with caplacizumab as early as possible, while trying to address the underlying autoantibody‐mediated inhibition of ADAMTS‐13 activity with immunosuppressives, which may take weeks to months. Most recent studies have demonstrated that adding caplacizumab to TPE and immunosuppressives is cost‐effective 69,80 . It allows the hospital to achieve a greater efficiency in managing a life‐threatening disease like iTTP.…”
Section: Therapeutic Strategy For Acute Ittpmentioning
confidence: 99%
“…Cost-effectiveness: Cost is one concern with the use of caplacizumab, which has been examined in several cost-effectiveness analyses [58][59][60]. In December 2020, after initial rejection, a series of meetings and re-appraisal of Sanofi's modeling at their fourth meeting, the National Institute for Health and Care Excellence (NICE) officially recommended caplacizumab use with TPE and immunosuppression for patients with immune TTP [58].…”
Section: Therapeutic #4: Caplacizumabmentioning
confidence: 99%
“…A 2021 Italian health technology assessment conducted a cost-effectiveness analysis of capalcizumab added to the standard of care versus the standard of care at a lifetime time-horizon, an Italian hospital perspective and at a willingness-to-pay threshold of 60,000 EUR/QALY previously suggested in Italy [59]. The authors reported an expected increase in 3.27 life years and 3.06 quality-adjusted life years with caplacizumab use at an incremental cost-effectiveness ratio of 44,600 EUR/QALY.…”
Section: Therapeutic #4: Caplacizumabmentioning
confidence: 99%